Design guidelines for generating augmented reality instructions - SILVA, Cledja Karina Rolim da (2016)
Most work about instructions in Augmented Reality do not follow established patterns or design rules – each approach defines its own method for conveying instructions. This work describes our results and experiences towards defining design guidelines for Augmented Reality instructions. From these guidelines, we propose a set of instructions and empirically validate them. The guidelines were derived from a survey of the most common visualization techniques and instruction types applied in Augmented and Mixed Reality. Moreover, we studied how instructions were done in 2D and 3D and how they can be applied in the Augmented Reality context. We observed that most work is related to object instructions and less work to body movement instructions. However, our proposal can be used in both cases. To validate our proposal we implemented a C⁺⁺ system, which -can be seen as a library to be used in different kinds of environments where the instructions of body and objects movements are important. A RGB-D sensor was applied to capture the movements. As result, we had visualization techniques applied together with typical AR instructions and indications of what kind of instruction could be used to: emphasize parts, indication of direction of the movement, management of occlusion, management of depth and feedback.